Optimizing the Asphalt Strength Quality with Kenpave Software to Improve Community Mobility: Case Study: Road Jampang Tengah – Kiara Dua - Muhammad Hidayat; Dio Damas Permadi; Neng Hodijatul Kubro; Ardin Rozandi; Utamy Sukmayu Saputri (Jurnal Teknik Sipil MACCA, 2025)
Jampang Tengah – Kiara Dua road (Km. Bdg 139 + 000 – 142 + 000) is a secondary arterial road which is a logistics route for products and services, allowing many heavily laden vehicles to pass through this road and the lack of maintenance causes this road to quickly become damaged . This research was conducted to provide a road redesign plan with flexible pavement using the 2017 Bina Marga road pavement design manual method with a structural evaluation of the kenvape program. Based on the results of research using the 2017 Bina Marga method, the thickness of the AC-WC pavement was 4 cm, the AC-BC layer was 13.5 cm, the CTB top foundation layer was 15 cm thick, and the class A bottom layer was 15 cm thick. cm. From the results of structural evaluation using the kenpave program, it was found that the strain value at a depth of 9.9997 cm would experience fatigue cracking of 0.0001914, for the horizontal strain value at a depth of 9.9997 cm there would be groove damage of 0.0003486, for the vertical strain value at a depth of 52.0003 cm will experience permanent damage to the flexible pavement structural layer of 0.0002147.